Designing a demand chain management framework under dynamic uncertainty: An exploratory study of the Chinese fashion apparel industry. Issue 1 (8th January 2018) - Ye, Ying; Lau, Kwok Hung
Abstract : Purpose: The purpose of this paper is to put forward a demand chain management (DCM) framework underpinned by the alignment theory and applies it to investigate the fashion apparel (FA) industry in China under the impacts of the latest economic transition. Design/methodology/approach: An exploratory multiple case study methodology involving five Chinese FA firms, each with a different business model and ownership type, was employed. Semi-structured interviews, onsite observations and review of company documents were conducted to collect information for analysis. Findings: Using a conceptual DCM framework as a guide for analysis, the study finds that companies with a higher level of alignment with the external market situation and among the three internal DCM dimensions, namely, market management, supply chain management (SCM), and organization management, appear to perform better under the rapidly changing economic conditions in China. Research limitations/implications: This study contributes to knowledge by reviewing thoroughly the literature on SCM evolution and develops a DCM framework based on alignment theory that represents the state of the art in this area. By extending the administration-integration-production-development (A-I-P-D) logic set adopted in the alignment theory, this study has also equipped the proposed framework with an empirical tool to measure alignment. Practical implications: By applying the framework to examine the Chinese apparel industry under the impacts of the latest economic transition, this study provides practitioners in the industry with a framework to help formulate strategies and a tool to measure alignment. The findings of the case study also offer insights to the industry to thrive in the rapidly changing businesses environment with dynamic uncertainties. Originality/value: This study extends the application of the A-I-P-D logic set under the alignment theory to the SCM field. This endeavor successfully transforms the proposed DCM framework from a theoretical concept to a practical tool to help evaluate empirically the alignment and strategic fit of a firm and potential relationship with firm performance. As the Chinese FA market has increasingly evolved under the impact of the globalization, the findings of this study not only assist the local FA companies in coping with the dynamic uncertainties but also shed light on the future developments of the global FA industry. Besides, the alignment measurement tool embedded in the proposed DCM framework can help enhance the chances of business success during implementation.